5 Strategic Talent Imperatives for the Boardroom. Issue 163 (17th May 2019) - Barrett, John; Buck, Bryan
Abstract : John Barrett and Bryan Buck are partners at the executive search firm ON Partners, where they work with public and private companies to identify and recruit high‐impact executives for board, C‐suite, and other senior leadership roles. Here, they discuss the ways that changing global conditions in 2019 and the foreseeable future are combining to create five strategic talent imperatives for the boardroom. Whether companies seek growth or transformation moving forward, their future success will rest to some degree upon their ability to create and maintain boards that meet these essential imperatives.